The Promises and Pitfalls of Sex Difference Research - Galea, Liisa AM (Front Neuroendocrinol, 2019)
Funding agencies in North America and Europe are recognizing the importance of the integration of sex differences into basic and clinical research. Although these mandates are in place to improve our knowledge of health for both men and women, there have been a number of implementation issues that require vigilance on the part of funders and the research community. Here we discuss issues on simple inclusion of both sexes in studies to specialisation of sex differences with attention paid to statistics and the need for sex-specific treatments. We suggest differing mandates need to be considered regarding simple integration versus the need for studies in the specialisation of sex differences and/or the need for research that recognises the importance of male-specific or female-specific factors that influence subsequent health such as menstruation, menopause or pregnancy.